Revista Enfermería Actual en Costa Rica: Una iniciativa para divulgar y compartir. - Rojas Valenciano, Ligia (2009)
The results of a documentary review on the creation of the Magazine Actual Nursing in Costa Rica, who was developed from a project of teaching no. 06 titleholder "Creation of the Magazine Present Nursing in Costa Rica", who concerns the School of Nursing of the University of Costa Rica. It was approved by the Vicerrectoria de Docencia of the same educational institution. (Vicerrectoría de Docencia motion VD1902-2000) The objective of this article is to disclose the diverse elements that are due to have present when creating, publishing and to maintain electronic magazine scientific, from the experience of the creators of the magazine. This investigation is framed within the foundations that the documentary investigation establishes. It began with a review of documents, among them the one of the project, information from the attendance at workshops, correspondence, meetings, published material and written communications. A matrix of data was elaborated with the purpose of to order them per dates and contents to realize an historical evolution and that made easy its later documentary analysis. Finally, one confronted all the data collected between the experiences of the creators of the magazine, the documentary analysis and the investigated theoretical material. The study evidence that the creation of an academic magazine scientific electronics requires of a planning that contemplates objectives, goals, reaches, experience, financial and logistic support, infrastructure resources and technology, trained personnel, cost/ benefit assessment, among others aspects; in order to assure a publication that has the quality that establishes the scientific parameters.